Performance Study of AODV and DSDV Routing Protocols for Mobile Ad Hoc Networks Based on Network Simulator NS2 - Mohammed, Marwan Aziz (Sulaimani Journal for Engineering Sciences, 2015)
Facebook Mobile Ad hoc Networks (MANET’s) is a self-configuring infrastructure less network of mobile devices connected by wireless . MANETs are a kind of Wireless ad hoc network that usually has a routable networking environment on top of a Link Layer . Route discovery and packet forwarding operations need an efficient routing protocol. Ad-Hoc on Demand Distance Vector Routing Protocol (AODV) and Destination Sequenced Distance Vector Routing protocol (DSDV) are counted as widely used routing protocols in MANET. In this paper we compare and evaluate the functionality of AODV and DSDV routing protocols. Simulation is based on NS2.34 network Simulator on Linux Fedora and the parameters are packet delivery ratio (PDR), Throughput and end-to-end delay. Simulation results show that AODV protocol is always superior as compared to DSDV protocol when using different number of nodes and scenario.
Keywords: MANET; Routing Protocol; AODV; DSDV; Comparative Study